Labor avoidance : the origins of inhumanity - Huer, Jon (Hamilton Books, 2015)
Jon Huer is professor of sociology at the University of Maryland University College. He has written over a dozen books of social criticism, including The Wages of Sin, Tenure for Socrates, Call from the Cave , and The Dead End , which TIME Magazine's Lance Morrow called "an important and often brilliant book."